Pengendali Putaran Turbin Pltmh Menggunakan Arduino - Okta Andrica Putra (Universitas Putra Indonesia YPTK Padang, 2020)
Research has been carried out to regulate / control the rotation of the turbine for this type of micro hydro power plant (PLTMH). This research was carried out during the dry season where water discharge greatly affects turbine rotation. This tool utilizes an optocoupler sensor, servo motor and 2x16 LCD. This system works based on the turbine rotation speed that is read on the sensor then controls the slope of the water fall using a DC motor. If thewater speed is low, the servo motor will turn CW up to a maximum slope of 75 degrees to produce maximum rotation and maximum power. This research does not focus on the magnitude of the resulting current source and the amount of water discharge